SYSTEM PROGRAMMING IN PHARMACEUTICAL MARKETING (International conference on multidisciplinary science, 2024)
This thesis about System Programming in Pharmaceutical Marketing. The overall aim of this study is to examine firm strategic choices that trigger negative externalities culminating in market failure, system crisis, and public harm.